ACHIEVING ONLINE SERVICE QUALITY THROUGH BUYER-SUPPLIER RELATIONSHIP MANAGEMENT - Angelia Nurgania Ellissa; Indita Aprilia; Zinggara Hidayat; Virienia Puspita; La Mani La Mani (Sean Institute, 2022)
The Internet has created new business opportunities, changed the boundaries of business processes, abolished the old information technology paradigm, and created a new environment for the global online economy. Here we can use online media in the form of social media and e-commerce as a medium to sell or market products to consumers. Social media has become very popular because it allows people to connect online through personal relationships, politics and business activities. The Indonesian market is estimated to consist of around US5 billion in regular retail, more than US3 billion in informal retail, and around 30 million online shoppers in 2017. Bank Indonesia has measured the value of online commerce in Indonesia. Online business is spreading in Indonesia which is commonly known as -commerce which means buying and selling transactions through the media using the internet. ease of shopping in e-commerce, can be done anytime and anywhere through online shopping. than that, in the form of online transactions, it can also be a distribution channel, saving time and costs, and reducing the obstacles experienced when shopping traditionally. Researchers who research the factors that can affect individuals when shopping online in Indonesia on achieving online service quality through buyer-supplier relationship management.